1986
DOI: 10.1111/j.1432-1033.1986.tb09455.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of three different flavodoxins from Azotobacter vinelandii

Abstract: The flavodoxins from Azotobacter vinelandii cells grown N2-fixing and from cells grown on NH40Ac have been purified and characterized. The purified flavodoxins from these cells are a mixture of three different flavodoxins (Fld I,11, 111) with different primary structures. The three proteins were separated by fast protein liquid chromatography; Fld I eluted at 0.38 M KC1, Fld I1 at 0.43 M KC1 and Fld I11 at 0.45 M KC1. The most striking difference between the three flavodoxins was the midpoint potential (pH 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
71
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 39 publications
(21 reference statements)
8
71
1
Order By: Relevance
“…Their oxidized absorption spectra show significant differences in the position of long-wave-length maxima (450 nm for R. capslulatlus and 460 nm for R. rubrum) which may reflect a slightly different arrangement of flavin mononucleotide in the protein. The analogous maxima for the nifspecific flavodoxins from K pneumoniae and A. vinelandii are found at 452 to 454 nm (7,20,25 (17). Thus, the flavodoxin isolated here is a real candidate for the physiological reductant of nitrogenase in R. capsulatus.…”
Section: Discussionmentioning
confidence: 78%
“…Their oxidized absorption spectra show significant differences in the position of long-wave-length maxima (450 nm for R. capslulatlus and 460 nm for R. rubrum) which may reflect a slightly different arrangement of flavin mononucleotide in the protein. The analogous maxima for the nifspecific flavodoxins from K pneumoniae and A. vinelandii are found at 452 to 454 nm (7,20,25 (17). Thus, the flavodoxin isolated here is a real candidate for the physiological reductant of nitrogenase in R. capsulatus.…”
Section: Discussionmentioning
confidence: 78%
“…The holoflavodoxin concentration was determined spectrophotometrically using an extinction coefficient of 11.3 mM Ϫ1 cm Ϫ1 at 452 nm (15). Apoflavodoxin was subsequently prepared by trichloroacetic acid precipitation (11, 16) followed by gel filtration on a Superdex 200 prep grade column (Amersham Biosciences) to remove apoflavodoxin molecules in an oligomeric state (13).…”
Section: Methodsmentioning
confidence: 99%
“…These gels give a better resolution but for unknown reasons the relative molecular mass of flavodoxin is slightly higher compared with the regular Laemmli gels. For molecular mass markers see the preceding paper [6]. Nitrogenase activity of whole cells was measured at different oxygen input rates as described earlier [15].…”
Section: Methodsmentioning
confidence: 99%
“…Recently it has been shown that A . vinelandii is able to make at least three different flavodoxins [6]. Flavodoxin I1 is most likely to be the reductant for nitrogenase [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation